International Scientific Conference Kitabistics - Research Methodology and Publication of Sources (Kitabistika - tyrimų elektrologija ir šaltinių publikavimas / Kitab Studies - Research Methodology and Source Publication) and the Exhibition The Way of Teachers: Research on the Culture of Lithuanian Nations as a Result of Cooperation between Kitabistic Schools of the Universities of Vilnius and Toruń (5- 6/10/2023, Vilnius University) - Kulwicka-Kamińska, Joanna (Slavistica Vilnensis, 2023)
On October 5–6, 2023, an international scientific conference Kitabistyka – metodologia badań i publikacja źródeł (Kitabistika – tyrimų metodologija ir šaltinių publikavimas / Kitab Studies – Research Methodology and Source Publication was held at the Faculty of Philology of Vilnius University. The conference was dedicated to the 55th anniversary of the publication of the work of Vilnius University professor A. Antonovich (1910–1980), devoted to Belarusian texts written in Arabic letters, as well as the 85th anniversary of Vilnius University professor Valery Chekmonas (1937–2004). The two-day conference was attended by 37 scientists from Lithuania, Poland, Estonia, Ukraine, Turkey and other countries. Plenary sessions and section work were thematically related to the research of Vilnius University professors. The speakers focused on the cultural heritage of the former Grand Duchy of Lithuania in the field of history, culture, language of the Tatars, Old Believers, as well as sociolinguistic Balto-Slavic studies, ethnolinguistics, and language contacts. The conference was preceded by a long history of cooperation between scientific centers of Lithuania and Poland. The exhibition dedicated to the two Professors in the Scientific Library of Vilnius University was presented.
Keywords: A. Antonowicz; Grand Duchy of Lithuania; V. Chekmonas; kitabistics; Vilnius university; Nicolaus Copernicus University